2015
DOI: 10.1111/brv.12217
|View full text |Cite
|
Sign up to set email alerts
|

Strontium isotopes (87 Sr/86 Sr) in terrestrial ecological and palaeoecological research: empirical efforts and recent advances in continental-scale models

Abstract: Strontium (Sr) isotope analysis can provide detailed biogeographical and ecological information about modern and ancient organisms. Because Sr isotope ratios ( Sr/ Sr) in biologically relevant materials such as water, soil, vegetation, and animal tissues predominantly reflect local geology, they can be used to distinguish geologically distinct regions as well as identify highly mobile individuals or populations. While the application of Sr isotope analysis to biological research has been steadily increasing, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 104 publications
2
55
0
Order By: Relevance
“…However, in contrast to C and O, the ultimate source of Sr in a given region is the local bedrock and therefore can be directly related to a geographical location. Recent work by Crowley et al showed that Sr isotopes in surface water, soil, vegetation, mammals, and fish across the continuous USA are generally close to the expected Sr isotopes based on the local water model. Although Sr geo‐referencing can be useful in modern ecological and archeological studies (e.g., ), the increasing globalization of the modern food supply is making 87 Sr/ 86 Sr less variable in modern human populations .…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…However, in contrast to C and O, the ultimate source of Sr in a given region is the local bedrock and therefore can be directly related to a geographical location. Recent work by Crowley et al showed that Sr isotopes in surface water, soil, vegetation, mammals, and fish across the continuous USA are generally close to the expected Sr isotopes based on the local water model. Although Sr geo‐referencing can be useful in modern ecological and archeological studies (e.g., ), the increasing globalization of the modern food supply is making 87 Sr/ 86 Sr less variable in modern human populations .…”
Section: Discussionmentioning
confidence: 83%
“…Recent work by Crowley et al showed that Sr isotopes in surface water, soil, vegetation, mammals, and fish across the continuous USA are generally close to the expected Sr isotopes based on the local water model. Although Sr geo‐referencing can be useful in modern ecological and archeological studies (e.g., ), the increasing globalization of the modern food supply is making 87 Sr/ 86 Sr less variable in modern human populations . In particular, Keller et al stated that the available Sr isotope data for modern US teeth show very little correlation with expected regional differences.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Although strontium sources are not completely homogenous in most environments, since more than 30 years (Ericson, ), 87 Sr/ 86 Sr values are widely used in ecology and bioarchaeology for reconstructing mobility of animals and humans (Crowley, Miller, & Bataille, ). Within archaeology, 87 Sr/ 86 Sr values are compared between early developing tissues (e.g., enamel) and the local environments where human bodies were buried, or tissues composed not long time prior to death of an organism (e.g., bone areas with high turnover rate).…”
Section: Introductionmentioning
confidence: 99%
“…The laboratory processing protocol for the measurement of 87 Sr/ 86 Sr in archaeological skeletons has been long established, and the isotopic variability per site well exceeds the isotopic variability of local individuals (±0.0003), with only a few exceptions . Moreover, it has been shown recently that the strontium isotopic signature of local water instead of soil leads to a far better predictability for the respective signature in the bones of large vertebrates. Therefore, we conclude that the measured 87 Sr/ 86 Sr isotopic ratios are also free of contaminants.…”
Section: Discussionmentioning
confidence: 99%